Students’ self-assessment of competencies in the phantom course of operative dentistry - Ciardo, Antonio; Möltner, Andreas (European journal of dental education, 2019)
Introduction The aim was to assess the competencies of undergraduate students in their roles of dental expert, scholar, communicator, collaborator, health advocate, manager and professional. Materials and Methods For this retrospective, pseudonymised observational study (pre-/post-testing), students in two cohorts in their first clinical semester in operative dentistry were asked to judge their competencies (1 = very good to 6 = insufficient) with a learning objective catalogue designed at the Goethe University Frankfurt (modelled after the National Competency-Based Learning Objective Catalogue Dentistry), at the beginning and end of their phantom course. In order to relate the students’ subjective competency judgements to objective evidence of their skills, at the end of the semester their marks from the summative Objective Structured Practical Examination (OSPE) were compared with the subjective judgement of their exam performance before the final results were known. Results The reliability of the evaluation sheet was evaluated with Cronbach's alpha 0.98. The students judged their competencies as “sufficient” (4.23 ± 0.51) at the beginning and “satisfactory” (2.82 ± 0.43) at the end. A significant improvement in competencies was observed within all roles. The students’ subjective judgement of the exam results (3.66 ± 0.62) was significantly correlated with the actual marks (3.69 ± 0.83) in the OSPE at 0.3547 (P = 0.0015). Conclusion The evaluation instrument showed excellent reliability. The students judged that their competencies significantly increased during the semester. The triangulation with the actual marks in the context of an OSPE demonstrated a significant correlation with the students’ exam judgements.
Gesehen am 21.05.2019